Penggunaan Teknik Molekuler untuk Mengenali Dermatofita yang Diisolasi dari Hewan Kesayangan di Jakarta dan Bogor - Endrawati, Dwi; Pribadi, Eko Sugeng; Indrawati, Agustin; Kusumaningtyas, Eni (Jurnal Veteriner; Vol 22 No 1 (2021), 2021)
Dermatophytosis is one of the superficial mycoses which causes skin health problems in pet animals. This study conducted molecular characterization using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) on specimens obtained from patients suspected of dermatophytosis in several clinics in DKI Jakarta Province and Bogor City. Fifty samples of skin scrapings from patients suspected of clinically dermatophytosis were collected and analyzed by conventional and molecular techniques. The Research aimed to identify dermatophyte that were isolated from pet animals  using PCR-RFLP technique.  The primers of ITS 1, ITS 4, Chytin Synthase, and cutting enzymes of Dde1 were used in this Research. Four specimens off 50 spesimens were tested positive using direct and culture PCR examination techniques. Based on the sequencing results, Microsporum canis was identified in four spesimens. Specimens that were positive for dermatophytes followed by RFLP using the Dde 1 enzyme. The results of the study showed that molecular techniques were a reliable way to determine the high-precision dermatophytes in diagnosing dermatophytosis. The Results also showed that molecular arrangement of B1 isolate was different from three other isolates.